2018
DOI: 10.1007/s12595-018-0282-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Fluoride Tolerant Bacillus spp (KT201599, KT201600) from the Midgut of Drosophila melanogaster: Their Probable Role in Fluoride Removal

Abstract: This is for the first time that two fluoride tolerant bacterial strains of Bacillus spp (KT201599 and KT201600) have been isolated from the mid-gut of third instar larvae of Drosophila melanogaster. They are characterized and identified using phenotypic characters and 16S rRNA gene based molecular phylogenetic analysis. Interestingly, KT201599 and KT201600 are able to survive at 2000-2500 lg/mL sodium fluoride (NaF) concentrations. The chronic lethal concentration 50 (LC 50 ) for NaF in Drosophila larvae is 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Two Fluoride tolerant bacterial strains, Bacillus sp . KT201599 and KT201600, were isolated from the mid-gut of third instar larvae of Drosophila melanogaster , which could survive at 2000–2500 µg/mL sodium Fluoride (NaF) concentrations and have the capability to remove Fluoride from the media by 16.66 and 24.71%, respectively [18] . Meanwhile, Fluoride resistant isolate H1 with high Fluoride resistance of 4 g/L in LB broth, purified in this study, showed 38.2% Fluoride removal activity from the media with NaF concentration of 250 mg·L −1 after incubation of 72 h at temperature 37 °C and initial pH 7.…”
Section: Discussionmentioning
confidence: 99%
“…Two Fluoride tolerant bacterial strains, Bacillus sp . KT201599 and KT201600, were isolated from the mid-gut of third instar larvae of Drosophila melanogaster , which could survive at 2000–2500 µg/mL sodium Fluoride (NaF) concentrations and have the capability to remove Fluoride from the media by 16.66 and 24.71%, respectively [18] . Meanwhile, Fluoride resistant isolate H1 with high Fluoride resistance of 4 g/L in LB broth, purified in this study, showed 38.2% Fluoride removal activity from the media with NaF concentration of 250 mg·L −1 after incubation of 72 h at temperature 37 °C and initial pH 7.…”
Section: Discussionmentioning
confidence: 99%